The founding of a peer-to-peer rental marketplace - marketing strategy - Bakali, Benjamin (2021)
This project illustrates the build-up of the start-up Renty a, a peer-to-peer renting platform for almost everything. This document is one of three individual contributions of the overall paper and follows the individual part “The founding of a Peer-to-Peer Rental Marketplace –Competitive Landscape and Operations”. This document describes the Marketing Strategy in detail. In the first section, relevant customer segments and personas are developed, and the different journeys one can have at https://www.rentya.de/are outlined. In the second part, key marketing and sales channels are identified, and the go-to-market strategy is developed.